2020
DOI: 10.3390/ijms21144875
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 by Natural Bioactive Compounds: A Promising Approach for Stroke?

Abstract: Stroke represents one of the main causes of disability and death worldwide. The pathological subtypes of stroke are ischemic stroke, the most frequent, and hemorrhagic stroke. Nrf2 is a transcription factor that regulates redox homeostasis. In stress conditions, Nrf2 translocates inside the nucleus and induces the transcription of enzymes involved in counteracting oxidative stress, endobiotic and xenobiotic metabolism, regulators of inflammation, and others. Different natural compounds, including food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 143 publications
0
28
0
1
Order By: Relevance
“…Nrf2 is a transcription factor which can regulate redox homeostasis in cells 33 . When activated under stress, it translocates from the cytoplasm to the nucleus and induces the transcription of downstream cytoprotective proteins 33,34 . Therefore, we analysed the distribution of Nrf2 in IEC‐6 cells by immunofluorescence assay.…”
Section: Resultsmentioning
confidence: 99%
“…Nrf2 is a transcription factor which can regulate redox homeostasis in cells 33 . When activated under stress, it translocates from the cytoplasm to the nucleus and induces the transcription of downstream cytoprotective proteins 33,34 . Therefore, we analysed the distribution of Nrf2 in IEC‐6 cells by immunofluorescence assay.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have highlighted the capacity of natural compounds derived from plants, vegetables, fruits, dietary nutrients, and endogenous molecules to be used as potential therapeutics for the treatment of neuroinflammation mainly owing to their antioxidant, anti-inflammatory, antiapoptotic, and neuroprotective effects ( Figure 2 ) [ 8 , 9 , 16 ]. Several studies have reported that many natural compounds can exhibit high affinity for various receptors in the brain, thereby specifically promoting or inhibiting various molecular signal transduction pathways and exerting multi-targeting effects on neuroinflammation-induced CNS disorders [ 55 , 56 ].…”
Section: Neuroprotective Effects Of Potential Natural Compounds Anmentioning
confidence: 99%
“…The advantages of many natural compounds in neuroinflammation involve their high affinity for various receptors in the brain, thereby specifically promoting or inhibiting various molecular signal transduction pathways and their multi-targeting effects on various CNS disorders as well as their lower side effects compared to conventional synthetic drugs [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, their pharmacological effects on neuroinflammation are often impeded because of their instability, poor solubility, and/or poor blood–brain barrier (BBB) permeability, resulting in lower bioavailability (BA), lower distribution in target tissue (brain), and higher systemic toxicities [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the major causes of disability and death worldwide, mainly affecting the elderly [1]. Most ischemic stroke cases are caused by reduced blood flow, due to arterial occlusion.…”
Section: Introductionmentioning
confidence: 99%